(untitled) (Boston, 2007)
Veterinary Toxicology is a unique single reference that teaches the basic principles of veterinary toxicology to any student at the DVM, MS or PhD level and will continue to serve as a clinical reference for practicing veterinary toxicologists, poison control centers, marine biologists, environmentalists, and animal scientists
Keywords: Veterinary toxicology,Toxicology,Veterinary Medicine,Dược lý thú y,Chất độc,Độc học thú y; Methods.,Phương pháp